Remembering tropical psychology's departed friend: Charles D. Spielberger. (1st September 2014) - Morgan, Robert F.
Abstract : It has been a year now since we lost Professor Spielberger. He was no stranger to congresses, higher education and research in tropical regions: Australia, India, Hong Kong, Japan, Singapore, Spain and Turkey to name a few. This international psychologist, so familiar to most of us, certainly deserves our review for his scientific and professional contributions. A master of diplomacy, and a wise mentor, we can now begin to see the full scope of his influence.